Discrete Element Method – Multi Body Dynamics Co-Simulation of a Vibrating Plate Compactor - Cronheden, Robin; Gustafsson, William (My University, 2026)
Physical testing can be a time consuming process. It is therefore desirable to reduce the need for physical testing by simulating procedures using computer aided engineering. Challenges arise when systems span multiple disciplines, hindering full modelling using a single method. The interaction between a vibrating plate compactor and a gravel substrate is an example of this type of system. Often this issue is resolved through simplification, to fit the model to a simulation environment at the cost of reducing physical accuracy. This thesis instead addressed the issue by separating incompatible parts of the model into two simulations and coupling them through co-simulation. Co-simulation enabled individual models to run separately in their respective solvers while facilitating communication between them. The aim was to develop a co-simulation that coupled a Multi-Body Dynamics model of the vibrating plate compactor and a Discrete Element Method model of the gravel substrate. The full model was validated against physical tests to ascertain how closely the co-simulation replicated them. It was found that certain aspects of the physical tests were captured. New insights into how the machine-substrate interaction works, not possible to glean from physical testing alone were also found. The results show that these models can be useful to enhance and to a degree replace physical testing. Certain interesting phenomena from the experiments were captured by the final coupled model, with some results matching very well and others showing slight missmatches. Our conclusion is that the final model works well as a proof of concept. Thereby motivating coupling of Multi-Body Dynamics - Discrete Element Method simulations when evaluating the performance of vibrating plate compactors.
Keywords: Co-simulation; DEM; MBD; Plate Compactor; Granular Materials